2011
DOI: 10.1097/mnm.0b013e32834654f8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial ischemia in collagen disease associated with pulmonary hypertension

Abstract: Coronary artery disease is a common association in patients with systemic lupus erythematosus and scleroderma, especially in those with pulmonary hypertension. This may reflect anatomical compression by distended pulmonary artery rather than diffuse ischemia or small vessel disease. It is important to determine the presence of coronary artery disease in these patients, which may be amenable to coronary stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Along with multiple reports of RV abnormalities in SSc, usually secondary to vascular and interstitial lung disease resulting into pulmonary hypertension [19,20], a primary LV involvement related to organic and functional alterations of microvasculature, including reduced coronary flow reserve, has been observed [21-24]; in support of these data, studies performed using single photon emission computerized tomography (SPECT) have shown multiple ventricular perfusion defects in the absence of coronary artery disease documented by angiography, particularly in patients with pulmonary hypertension [25,26]. Owing to this vasculopathy, a “patchy” myocardial fibrosis develops, with a distribution unrelated to coronary vessels territories [27-30], leading, as consequences, to multiple LV diastolic and systolic abnormalities including lower TDI velocities and impaired myocardial deformation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Along with multiple reports of RV abnormalities in SSc, usually secondary to vascular and interstitial lung disease resulting into pulmonary hypertension [19,20], a primary LV involvement related to organic and functional alterations of microvasculature, including reduced coronary flow reserve, has been observed [21-24]; in support of these data, studies performed using single photon emission computerized tomography (SPECT) have shown multiple ventricular perfusion defects in the absence of coronary artery disease documented by angiography, particularly in patients with pulmonary hypertension [25,26]. Owing to this vasculopathy, a “patchy” myocardial fibrosis develops, with a distribution unrelated to coronary vessels territories [27-30], leading, as consequences, to multiple LV diastolic and systolic abnormalities including lower TDI velocities and impaired myocardial deformation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been described that the development of pulmonary fibrosis is associated with increased pulmonary vascular resistance [28]; however, in patients with RL this is a concomitant disorder and not the primary cause of exercise limitation. Moreover, it is not unusual for patients with SSc-associated pulmonary arterial hypertension to present with concomitant primary or secondary left heart disease [29,30,31]; thus the utilization of CPET is necessary for the differentiation between the PV, RL and LVD groups. PET CO 2 reflects the ability of the cardiopulmonary system to discard excessive carbon dioxide produced during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients did not undergo angiography, so sensitivity, specificity, and predictive values were not available. In the study of El-Shafie et al, 16 only one of six patients with LV segmental perfusion defects had CAD at angiography, for a positive predictive value of only 16%. This suggests that there remains much to be learned about the interpretation of MPI in PH patients.…”
Section: Next Stepsmentioning
confidence: 92%
“…PH had, at one point, been considered a contraindication to stress testing. 19 In patients with moderate degrees of PH, as in the study by El-Shafie et al, 16 patients may be able to exercise to an adequate hemodynamic end point. However, as PH becomes more pronounced, as in the group represented by Gomez et al, 12 this becomes less likely, and pharmacologic stress testing is necessary.…”
Section: Pharmacologic Stress Testing Using Selective A2a Receptor Agmentioning
confidence: 97%
See 1 more Smart Citation